PENERAPAN STRATEGI “LESSER” DALAM PEMBELAJARAN MENULIS KARANGAN BAHASA JEPANG (SAKUBUN) MAHASISWA TINGKAT IIIPRODI PENDIDIKAN BAHASA JEPANGFKIP UNIVERSITAS RIAU - Widiati, Sri Wahyu Widiati Wahyu; Budiani, Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research is to find outthe difference of students’ ability in writing Japanese essays(sakubun) after using LESSER strategy. This research is a weak-experiment type one group pretest post test design. The object of this research is 15 third-level students as the responsents.Data collection was performed by giving test. The given test was writing assignments in order to find out the students’ ability of content and organization aspect in writing Japanese essays (pretest and post test). This research is processed by paired sampling t-test using software of SPSSVersion 22to get the value of the significant. Based on the data analysis, the value of the post test of content and organization in writing Japanese essays is lower than 0,05 (0,01<0,05 and 0,024<0,05), It means that Ha is accepted and Ho is rejected, so there is a significant impact with the applicaation oh LESSER strategy on the learning of Japanese writing (sakubun) by the third level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University. Key Words:sakubun, strategy, LESSER